2022
DOI: 10.3390/su14138212
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Forms of the Economic Effects of Renewable Energy Consumption: Evidence from China

Abstract: Renewable energy’s economic effects have been hotly debated, as it is a promising energy source. However, scholars have not achieved an agreement on this hot topic. Therefore, this article re-examines the direct and indirect economic effects of renewable energy consumption in China from 1990 to 2020. Using the Granger causality test to conduct empirical analysis, the result suggests there is a bidirectional causality between renewable energy consumption and economic growth. Then, the mediation model is used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Moreover, the results in Table 3 also suggest that a two-way causality between fossil fuel energy and the gross domestic product exists. In addition, this feedback hypothesis is supported by Chontanawat et al [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 66%
“…Moreover, the results in Table 3 also suggest that a two-way causality between fossil fuel energy and the gross domestic product exists. In addition, this feedback hypothesis is supported by Chontanawat et al [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 66%
“…Examining the factors affecting REC, [44] suggested that GDP and institutional factors affect the level of REC across 41 European countries, while the environmental component only has a negligible impact on non-extractive countries. Moreover, some studies have found that other factors, such as trade openness, appear to have a statistically significant impact on REC [71].…”
Section: Plos Onementioning
confidence: 99%
“…When compared to infinite energy, it is a subset of the latter. Following He and Zhang [32], He and Huang [33], He et al [34], He [35], and He and Zhang [36], renewable energy consumption is used as an independent variable in this article.…”
Section: Variable Descriptionmentioning
confidence: 99%